Trends in criminal policy: (dis) organising the chaos. Criminalisation vs decriminalisation (institutional approach) - Туляков, В. О.; Туляков, Вячеслав Олексійович; Tuliakov, Viacheslav O. (Ciudad Real, 2023)
• The state as a criminal • Territories under official control (effective governance and occupation) • Substabtional criminal law in search of balance between security of people and state`s security • Civil society, mad printer politics and criminal law
Tuliakov V. О. Trends in criminal policy: (dis) organising the chaos. Criminalisation vs decriminalisation (institutional approach) [Electronic resource] : lecture 4 : [presentation PowerPoint] / V. О. Tuliakov. – Electronic data (20 slides). – Ciudad Real, 2023. – Режим доступу : https://hdl.handle.net/11300/25983
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; state; criminal; effective governance; occupation; Substabtional criminal law; security of people; state`s security; Civil society; criminal law